(untitled) (Ius Novum, 2019)
In accordance with Article 5 of the Constitution, the Republic of Poland safeguards the national heritage, which is a constitutional value, in the same way as it safeguards independence. The national heritage can be understood as culture rooted in the Christian heritage of the Nation, as it is laid down in the Preamble, or cultural heritage referred to in Article 6 para. 2 of the Constitution. This latter concept seems to be an integral part of the national heritage. The national heritage cannot, as it has been proved, be perceived as the heritage of the Polish ethnic nation, although the term “nation” used in the Constitution can be interpreted in various ways. In practice, the status of national minorities’ cultural heritage and whether it is part of the Polish national heritage also constitute a problem.